IMPLEMENTASI MODEL PBL BERBANTUAN GAME EDUKASI TERHADAP KAMAMPUAN PEMECAHAN MASALAH MATEMATIS DAN HABITS OF MIND SISWA SMP MATERI SPLDV - Fahirah, Eka Candra Zuhrotul; Mawarsari, Venissa Dian; Suprapto, Rohmat (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
ABSTRACT The ability of junior high school students to solve mathematical problems related to Two-Variable Linear Equation Systems (SPLDV) remains quite low, primarily due to a focus on teacher-led instruction and the limited participation of students. This research aims to evaluate how effective the Problem Based Learning (PBL) approach, supported by the Wayground educational game, is on enhancing students’ skills in solving math problems, as well as to assess how Habits of Mind (HoM) affect those skills. A quantitative method was applied, utilizing a nonequivalent control group layout, with the study participants drawn from three classes sharing similar variance; specifically, class VIII A served as the experimental group, class VIII C acted as the control class, while class VIIID was designated for the instrument trial. The tools for this research included a test to measure mathematical problem-solving capabilities and a questionnaire on HoM. Analysis of the data was conducted using nonparametric techniques, such as the Wilcoxon Signed Rank test, the Mann–Whitney U test, and the Spearman correlation test. Findings from the research revealed that the PBL approach, when paired with the Wayground educational game, significantly improved students’ math problem-solving abilities, achieving a classical completeness rate of 80. 77%. Moreover, there was a notable distinction in math problem-solving skills between the experimental and control classes, although HoM did not show a significant impact on students’ mathematical problem-solving abilities.